See one, do one, teach one: Reimagining reproductive endocrinology and infertility training programs to expand access to care - Jacob P. Christ, M.D; Michelle Vu, M.D; Holly Mehr, M.D., M.S.Ed; Tia Jackson-Bey, M.D., M.P.H; Christopher N. Herndon, M.D (Elsevier, 2022)
Objective: To provide a review of the current literature surrounding barriers to reproductive medicine and present examples of how resident and fellow education can be used to overcome these barriers. Design: A review of the relevant literature addressing barriers to reproductive medicine, resident and fellow education, and related materials was completed. Setting: Academic medical institutions. Patient(s): None. Intervention(s): None. Main Outcome Measure(s): Health disparities and barriers in access to care. Result(s): Of barriers in access to care, 3 were reviewed in detail: cost of health care, racial inequities, and marginalization of immigrant communities. The suggested strategies to mitigate these barriers include the following: reducing racial inequities through improved diversity within reproductive medicine and through antiracism training, developing opportunities for trainees to engage in advocacy, strengthening reproductive endocrinology and infertility clinical exposure and educational curricula in training programs, inclusion of residents and fellows in clinical care, and improving the accessibility of fertility care through implementing approaches to optimize the management of infertility in challenging, resource-constrained settings. Conclusion(s): Infertility is one of the most prevalent reproductive health diseases, yet profound disparities and inequities in access to care exist today in the United States. Lower-income, minority, and immigrant communities are among those most marginalized. Improved access to care begins with broadened obstetrics and gynecology and reproductive endocrinology and infertility trainee education, which acknowledges the barriers these communities face and provides strategies to help overcome these obstacles to care.